Pampia: A large cratonic block missing in the Rodinia supercontinent - Ramos, Victor Alberto (2010)
The large cratonic block of Pampia, at present in southern South America, is commonly missing in recent comprehensive reconstructions of Rodinia. This block was the conjugate margin of the Amazonia craton that corresponds to the W-NW-trending segment of the Sunsás orogen. This segment developed between Sucre in Bolivia and Corumbá in Brazil as a result of a Mesoproterozoic collision. The western margin of Pampia partially coincides with the southern part of the Arequipa-Antofalla terrane that was also amalgamated during the Mesoproterozoic. The Cuyania terrane, a Laurentian rifted continental block, was accreted to the southern sector of this margin of Pampia in middle Ordovician times. The northern sector of the eastern margin of Pampia is the lower plate of the Brasiliano belt developed along the Paranapanema craton during the early Cambrian collision associated with the closure of the Clymene Ocean. The southern sector of the eastern margin partially coincides with the southern extension of the Transbrasiliano lineament, which juxtaposed the Rio de La Plata Craton with the Pampia cratonic block. Along this eastern margin the Pampean-Paraguay orogen was formed during the late Brasiliano cycle in latest Proterozoic-Early Cambrian time. The southern margin was generated by the collision of Patagonia during late Paleozoic times. This cratonic block of Pampia, so defined, has western and northern sectors formed by Mesoproterozoic orogens, while the eastern sector is partially formed by juvenile Neoproterozoic crust, although older rocks cannot be ruled out. The Pampia cratonic block was the locus of several magmatic belts associated with important metamorphism during the Paleozoic and preserved in the central part at lower crustal levels.